Ultraviolet irradiation suppresses T cell activation via blocking TCR-mediated ERK and NF-κB signaling pathways - Li-Weber, Min; Krammer, Peter H. (The journal of immunology, 2005)
UV irradiation is carcinogenic and immunosuppressive. Previous studies indicate that UV-mediated alteration of APCs and induction of suppressor T cells play a critical role in UV-induced immune suppression. In this study, we show that UV irradiation can directly (independently of APCs and suppressor T cells) inhibit T cell activation by blocking TCR-mediated phosphorylation of ERK and IκB via overactivation of the p38 and JNK pathways. These events lead to the down-modulation of c-Jun, c-Fos, Egr-1, and NF-κB transcription factors and thereby inhibit production of cytokines, e.g., IL-2, IL-4, IFN-γ, and TNF-α, upon TCR stimulation. We also show that UV irradiation can suppress preactivated T cells, indicating that UV irradiation does not only impair T cell function in response to T cell activation, but can also have systemic effects that influence ongoing immune responses. Thus, our data provide an additional mechanism by which UV irradiation directly suppresses immune responses.
Gesehen am 04.03.2021